Resistant Hypertension: A Clinical Case (2018)
Introduction: Secondary hypertension corresponds to 15 % of the causes of arterial hypertension, and among them, primary hyperaldosteronism presents a variable incidence of about 3% in hypertensive patients. It has a slightly higher prevalence in women, between 30 and 60 years, and is usually unilateral. Case presentation: The authors describe the clinical case of a patient, followed by severe hypertension medicated with four antihypertensive drugs for tension stabilization, maintaining systolic arterial tensions superior to 170 mmHg. In the aetiological study of hypertension, analytical alterations suggested hyperaldosteronism and a nodular lesion was detected in the left adrenal gland. The patient was submitted to surgery and excision of the lesion was done with histological confirmation of the diagnosis of corticomedullary adenoma of the adrenal gland. The patient presented improvement of the tension profile, with the need to suspend two of the four antihypertensive drugs and to reduce the dose of the remaining ones. Conclusion: A tumor of the adrenal cortex producing aldosterone is the main cause of primary hyperaldosteronism and should always be excluded when the presence of di cult to control, severe hypertension is detected, since the standard treatment is surgical, leading to a stabilization of the tension pattern after a few months.